Microwave-vacuum drying of round bamboo: A study of the physical properties - Lv, Huang-Fei; Ma, Xin-Xin; Zhang, Bo; Chen, Xiu-Fang; Liu, Xian-Miao; Fang, Chang-Hua; Fei, Ben-Hua (Construction & building materials, 2019)
•Microwave-vacuum drying offers a novel way for round bamboo drying.•Some physical properties of bamboo after microwave-vacuum drying are investigated.•Microwave-vacuum drying shows good potential for round bamboo culm drying. Rapid and clean drying of round bamboo is a highly desired process in utilizing bamboo resources. The properties of dried round bamboo (Phyllostachys iridescens C.Y.Yao & S.Y.Chen), such as moisture content, color, shrinkage and cracking, under different microwave-vacuum drying conditions were investigated in this study. The results showed that the drying rate of round bamboo increased with drying temperature, microwave power and vacuum level. The chromatic parameters gradually deepened as the drying temperature increased. The surface color changed from green to yellow after drying. The shrinkage of samples increased proportionally with temperature, microwave power and vacuum level, and the shrinkage in the top section was greater than in the bottom one. The cracking ratio of round bamboo was low when using microwave-vacuum drying technology, demonstrating that this technology can largely avoid the occurrence of cracking and obtain rapid drying of round bamboo.